Rapid Gene Concatenation for Genetic Rescue of Multigene Mutants in Candida albicans - Manning Y. Huang (American Society for Microbiology, 2018)
ABSTRACT The biological function of a gene is often probed through its interactions with other genes. This general approach has been especially useful to build knowledge about poorly understood genes upon the bedrock of well-characterized genes. Genetic interaction analysis requires the construction of strains with mutations in two or more genes. Single-gene mutants of microbial pathogens are generally validated through introduction of a wild-type copy of the affected gene to create a complemented or reconstituted strain, followed by testing for restoration of a wild-type phenotype. This practice, formalized as one of Falkow’s “molecular Koch’s postulates” ensures that the phenotype of the mutant depends upon the known mutation. However, multigene mutants are seldom validated because of the labor required to assemble multiple genomic segments into a vector that can be introduced into the mutant strain. We present here an approach, concatemer assembly for rescue of mutant abilities (CARMA), that circumvents this impediment through an in vivo recombinational assembly strategy that does not require cloning at all. Our results show that CARMA allows genetic rescue of two double-gene mutant strains of the fungal pathogen Candida albicans. IMPORTANCE Our understanding of new genes is often built upon the knowledge of well-characterized genes. One avenue toward revealing such connections involves creation of strains with mutations in two or more defined genes to permit genetic interaction analysis. Strain manipulations can yield unexpected mutations at loci outside the defined targeted genes. In this report, we describe a method for rapid validation of multigene mutants, thus allowing an appraisal of the contribution of the defined targeted genes to the strain’s phenotype.